High-frequency Pairs Trading on a Small Stock Exchange - Mikkelsen, Andreas; KjÃ¦rland, Frode (International Journal of Economics and Financial Issues, 2018)
We study the performance of a high-frequency pairs trading strategy on the 100 most liq- uid stocks, in 15-minute intervals, on a small commodity dominated stock exchange (Oslo Stock Exchange) using a comprehensive dataset from January 2012 to March 2016. We use both the dis- tance and cointegration approach. Moreover, we let the formation (trading) period vary between two (one), four (two), and six (three) weeks, in order to test the impact on the pairs trading profit. We find that the distance and cointegration approaches both have their strenghts and weaknesses. In addition, we find that a shorter formation (and trading) period yields better results. As a further contribution to the literature, our findings imply that a simple static pairs trading strategy, still is profitable using high-frequency data. Further, our results show better performance in a bull market than in a sideways-moving, volatile market. Keywords: Finance, Pairs trading, Statistical arbitrage, High-frequency trading, Distance method, Cointegration JEL Classifications: G11, G15